Деструктивний інформаційний вплив у Стародавньому Китаї - Черниш, Роман Федорович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
An urgent problem today for ensuring international and national security is prompt response to the emergence of new threats in various spheres of public life (including the information sphere). The problem of destructive information influence and its countermeasures has been relevant since ancient times. In our opinion, in the course of organizing an effective response to the destructive informational influence exerted by the russian federation in the conditions of the russian-Ukrainian war, it is necessary to take into account, including, previous experience with reference to the realities of today: communication channels, methods of distribution, environment, efficiency proving information, etc.